ELLIPSIS ON GADGET ADVERTISEMENTS IN T3 MAGAZINE - Cayestu, Teresa Avilla Ayuning Budi; Pasaribu, Truly Almendo (Yayasan Visi Intan Permata, 2020)
This research aims at analyzing the ellipsis and its recoverability in T3 gadget magazine issued on December 2018 based on Swan?s (1996) and Quirk?s (1985) domains of ellipsis. This qualitative-descriptive research investigated 107 clauses found in the advertisement containing 509 ellipses. The data were gathered by close and careful reading and coded using a checklist table developed based on the domains of ellipsis. The research found that ellipsis type 2 (ellipsis structured with and, but and or) were dominant in the data as the omission aimed to avoid repetition and be concise. There were only 2 out of 14 ellipsis types which were absent, namely type 6 and 14. The ellipsis types that were being analyzed happened to have three types of recoverability, namely textual, structural, and situational recoverability. The majority of the data used textual recoverability or the recoverability parts are recovered by the other part within the clause or nearby clauses. This research discusses the interface between syntax and semantics that although the syntactic forms are changed through ellipsis, users can still recover the meanings.